Pulmonary mucosa-associated lymphoid tissue lymphoma revisited. Issue 4 (October 2016) - Catherinot, Emilie; Longchampt, Elisabeth; Ferroni, Agnès; Rivaud, Elisabeth; Cahen, Pierre; Couderc, Louis-Jean
We read with great interest the review of Borie et al. [1] on pulmonary lymphoma of the mucosa-associated lymphoid tissue (MALT). We agree with the hypothesis that chronic antigen stimulation of microbial origin may lead to the development of pulmonary MALT lymphoma. Indeed, MALT lymphoma has been associated with various chronic infections in extrapulmonary localisations. This link has previously been demonstrated between Helicobacter pylori infection and gastric MALT lymphoma, and suggested with Campylobacter jejuni, Chlamydia psittaci and Borrelia burgdorferi with small intestine lymphoma, ocular annexa lymphoma and cutaneous lymphoma, respectively. Similarly a link has recently been suggested between infection with Achromobacter xylosoxidans and pulmonary MALT lymphoma [2]. Our results do not suggest a link between mycobacteria and pulmonary MALT lymphoma: high-speed sequencing is needed http://ow.ly/xXXm301AQ6r